Analisis Network Planning Dan Crash Program Pada Proyek Pembangunan Rumah Susun Yayasan Pondok Modern Al Kautsar - Ermiyati Ermiyati; Fakhri Fakhri; Suprasman Suprasman; Firdi Mulyadi (Mahesa Research Institute, 2022)
The cause of project delays in terms of planning and scheduling is the management aspect. To avoid project delays, Yayasan Pondok Modern Al Kautsar development project was delayed due to lack of manpower, changes in work items, and difficulty getting into the project so that one alternative was needed, namely analysis of Network Planning with Critical Path Method (CPM), Project Evaluation and Review Technique (PERT) and Crash Program. Alternatives are the increase in the amount of labor to get maximum acceleration and the addition of alternative minimum costs. Implementation of acceleration with Critical Path Method (CPM), Project Evaluation and Review Technique (PERT) and Crash Program and using Micorosft Project 2019 software to facilitate in analyzing Network Diagrams and determining critical trajectories. The alternative goal is to find out how many days the project schedule can be accelerated and the cost of acceleration. The initial planning of the project was carried out for 198 days at a cost of Rp. The 6.738.000.841,66. most optimal alternative is Crash Program 2 with a maximum acceleration increase of 2 days with a project completion time of 196 days with an acceleration cost of Rp. 59,580,000.